FORMATION OF IMMUNITY AGAINST SARS-COV-2 AMONG EMPLOYEES OF A LARGE GENERAL HOSPITAL - Михаил Исаакович Ликстанов; Светлана Анатольевна Кузьменко; Григорий Валерьевич Вавин; Оксана Владимировна Коваливнич; Вадим Гельевич Мозес; Кира Борисовна Мозес; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Евгений Владимирович Лишов (Медицина в Кузбассе)
The article presents an analysis of the formation of immunity against SARS-CoV-2 among employees of a large multidisciplinary hospital.